Zn-Zr co-doped yttrium-magnesium composite ceramic powder as well as preparation method and application thereof

By doping Zn and Zr in yttrium magnesium composite ceramics, optimizing process conditions, and preparing high transmittance and high strength Zn-Zr co-doped yttrium magnesium composite ceramic powder, the existing materials are solved in a high Mach environment The problem of insufficient intensity and transmittance is suitable for infrared window materials for hypersonic aircraft.

CN119161185APending Publication Date: 2024-12-20成都东骏激光股份有限公司

Patent Information

Application Number
CN202411355589.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing infrared ceramic window materials cannot meet the requirements of intensity, low radiation, low optical loss and high transmittance in high Mach environments in hypersonic aircraft.

Method used

Using Zn-Zr co-doped yttrium magnesium compound-phase ceramic powder, nano-scale powders of yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide are prepared through sol gelation, combustion, calcination and ball milling to optimize their volume. The ratio and particle size distribution improve the transmittance and bending strength of the ceramic.

Benefits of technology

The high transmittance and strength of ceramics are achieved, with a bending strength greater than 400MPa, and a transmittance of more than 80% to wavelengths of 1.5μm-7μm light. It is suitable for infrared window materials in high Mach environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063517640000091
    Figure BDA0005063517640000091
  • Figure BDA0005063517640000101
    Figure BDA0005063517640000101
Patent Text Reader

Abstract

The invention discloses Zn-Zr co-doped yttrium-magnesium multiphase ceramic powder and a preparation method and application thereof.The Zn-Zr co-doped yttrium-magnesium multiphase ceramic powder comprises yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide, the volume ratio of yttrium oxide to magnesium oxide is 0.9-1.2: 1, and the mass ratio of zinc oxide to zirconium oxide is 1: 1-5; in the Zn-Zr co-doped yttrium-magnesium composite ceramic powder, the total mass fraction of zinc oxide and zirconium oxide is less than 15%. According to the embodiment of the invention, Zn and Zr are doped in the yttrium-magnesium multiphase ceramic powder, Zn replaces Mg, Zr replaces Y, and Zn-Zr is doped, so that the refractive index of a magnesium oxide phase is improved, the refractive index difference between the magnesium oxide phase and an yttrium oxide phase is reduced, and the transmittance of the ceramic prepared from the yttrium-magnesium multiphase ceramic powder is improved; meanwhile, Zn and Zr are doped, so that solid solution toughening is facilitated, the material strength is improved, and the bending strength of the prepared ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite ceramics, and in particular to Zn-Zr co-doped yttrium-magnesium composite ceramic powder and a preparation method and application thereof. Background Art

[0002] At present, common infrared ceramic window materials include sapphire (Al2O3), aluminum oxynitride (AlON), spinel (Mg2AlO4), zirconium oxide (ZrO), magnesium fluoride (MgF2), zinc sulfide (ZnS), yttrium oxide (Y2O3), etc., but none of them can meet the application performance requirements of infrared windows of hypersonic aircraft. Yttrium magnesium composite ceramics are one of the newly studied high-strength, low-radiation infrared window materials suitable for service in high Mach environments.

[0003] The current yttrium-magnesium composite ceramics are basically pure phase or doped with Zn, with limited improvements in transmittance and strength. Higher strength, smaller grain size, smaller optical loss coefficient and more efficient light conversion efficiency are still needed to meet the needs of window materials serving in high Mach environments.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide Zn-Zr co-doped yttrium-magnesium composite ceramic powder and its preparation method and application, so as to improve the transmittance and strength of the material.

[0006] The present invention is achieved in that:

[0007] In a first aspect, the present invention provides a Zn-Zr co-doped yttrium-magnesium composite ceramic powder, comprising yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide, wherein the volume ratio of yttrium oxide to magnesium oxide is 0.9-1.2:1, and the mass ratio of zinc oxide to zirconium oxide is 1:1-5; in the Zn-Zr co-doped yttrium-magnesium composite ceramic powder, the total mass fraction of zinc oxide and zirconium oxide is less than 15%.

[0008] In an optional embodiment, the average particle size of the Zn—Zr co-doped yttrium magnesium composite ceramic powder is less than 10 nm.

[0009] In a second aspect, the present invention provides a method for preparing the Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to the aforementioned embodiment, comprising:

[0010] The solution including yttrium salt, magnesium salt, zinc salt and zirconium salt is subjected to sol-gelation, combustion and calcination in sequence to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic powder;

[0011] Alternatively, a mixture of yttrium-magnesium composite ceramics, zirconium oxide and zinc oxide is ball-milled to obtain the Zn—Zr co-doped yttrium-magnesium composite ceramic powder.

[0012] In an optional embodiment, the sol-gelling comprises: mixing an aqueous solution containing yttrium nitrate, magnesium nitrate, zinc nitrate and zirconium nitrate with citric acid and ethylene glycol, and keeping the mixture at 40-100° C. for 4-36 hours;

[0013] Preferably, the molar ratio of magnesium ion to citric acid is 0.5-1;

[0014] Preferably, the molar ratio of magnesium ions to ethylene glycol is 0.25-0.75;

[0015] Preferably, the molar ratio of yttrium nitrate to magnesium nitrate in the aqueous solution is 0.5-0.7.

[0016] In an optional embodiment, the combustion step temperature is 100°C-300°C, and the combustion time is 1h-5h;

[0017] And / or, the calcination step temperature is 500° C.-700° C., and the calcination time is 5 h-20 h.

[0018] In an optional embodiment, the average particle size of the yttrium-magnesium composite ceramic is less than 10 nm;

[0019] And / or, the particle size of the zirconium oxide and zinc oxide is less than 40 nm.

[0020] In an optional embodiment, the ball-to-material ratio in the ball milling step is 1:5-9, the diameter of the ball mill is 0.5-3 mm, the ball milling speed is 100-250 rad / min, and the ball milling time is 10-30 h;

[0021] And / or, a dispersant is also added during ball milling, and the mass ratio of the dispersant to the oxide is 1.5-3:1.

[0022] In a third aspect, the present invention provides a method for preparing a Zn-Zr co-doped yttrium-magnesium composite ceramic, comprising: sintering the Zn-Zr co-doped yttrium-magnesium composite ceramic powder described in the aforementioned embodiment to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic.

[0023] In an optional embodiment, the sintering temperature is 1100° C.-1400° C., and the sintering time is 1.5 h-3 h.

[0024] In a fourth aspect, the present invention provides a Zn-Zr co-doped yttrium-magnesium composite ceramic prepared by the method described in the aforementioned embodiment, wherein the average grain size of the Zn-Zr co-doped yttrium-magnesium composite ceramic is less than 150 nm;

[0025] And / or, the density of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 99.95%;

[0026] And / or, the flexural strength of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 400 MPa;

[0027] And / or, the transmittance of the Zn—Zr co-doped yttrium magnesium composite ceramic to light with a wavelength of 1.5 μm-7 μm is greater than 80%.

[0028] The present invention has the following beneficial effects:

[0029] In an embodiment of the present invention, Zn and Zr are doped into yttrium-magnesium composite ceramic powder, wherein Zn replaces Mg and Zr replaces Y. The incorporation of Zn-Zr is beneficial to increasing the refractive index of the magnesium oxide phase and reducing the refractive index difference between the magnesium oxide phase and the yttrium oxide phase, thereby improving the transmittance of the ceramics prepared therefrom; at the same time, doping with Zn and Zr is beneficial to solid solution toughening, improving material strength, and improving the flexural strength of the ceramics prepared therefrom. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0031] An embodiment of the present invention provides a Zn-Zr co-doped yttrium-magnesium composite ceramic powder, comprising yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide, wherein the volume ratio of yttrium oxide to magnesium oxide is 0.9-1.2:1, and the mass ratio of zinc oxide to zirconium oxide is 1:1-5; in the Zn-Zr co-doped yttrium-magnesium composite ceramic powder, the total mass fraction of zinc oxide and zirconium oxide is less than 15%.

[0032] Under normal pressure, the mutual solubility of the Y2O3–MgO system is low, and it is a stable two-phase mixture below 2110°C. Therefore, during the ceramic sintering process, an appropriate amount of MgO can be introduced into the nano Y2O3 powder as a second-phase grain growth inhibitor, and the pinning effect and interface effect of the two-phase grains can be fully utilized to inhibit the rapid growth of the grains, thereby ensuring that the grains of the final ceramic sample are in nanometer size. The grain boundaries of the Y2O3 phase and the MgO phase contact each other, inhibiting the rapid growth of each other's grains. The more obvious the pinning effect of the two phases, the greater the inhibitory effect on grain growth. In order to achieve the best pinning effect of the two phases, the uniform distribution of the Y2O3 and MgO phases should be promoted, and the volume ratio should be close to 1:1. The smaller the grain size, the better the effect.

[0033] In an embodiment of the present invention, Zn and Zr are doped into yttrium-magnesium composite ceramic powder, wherein Zn replaces Mg and Zr replaces Y. The incorporation of Zn-Zr is beneficial to increasing the refractive index of the magnesium oxide phase and reducing the refractive index difference between the magnesium oxide phase and the yttrium oxide phase, thereby improving the transmittance of the ceramics prepared therefrom; at the same time, doping with Zn and Zr is beneficial to solid solution toughening, improving material strength, and improving the flexural strength of the ceramics prepared therefrom.

[0034] In an optional embodiment, the average particle size of the Zn—Zr co-doped yttrium magnesium composite ceramic powder is less than 10 nm.

[0035] The present invention also provides a method for preparing the Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to the above embodiment, comprising:

[0036] The solution including yttrium salt, magnesium salt, zinc salt and zirconium salt is subjected to sol-gelation, combustion and calcination in sequence to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic powder;

[0037] Alternatively, a mixture of yttrium-magnesium composite ceramics, zirconium oxide and zinc oxide is ball-milled to obtain the Zn—Zr co-doped yttrium-magnesium composite ceramic powder.

[0038] Among them, a solution including yttrium salt, magnesium salt, zinc salt and zirconium salt is sequentially subjected to sol-gelation, combustion and calcination to obtain the Zn-Zr co-doped yttrium magnesium composite ceramic powder with relatively small particle size, and the raw materials can be relatively evenly mixed. The yttrium salt, magnesium salt, zinc salt and zirconium salt can be directly purchased from the market and configured into a solution, or partly or completely prepared by reacting the corresponding oxides with acids. The effect is not much different, but preparing the salt solution by reacting the oxides with acids is beneficial to reducing production costs.

[0039] The Zn-Zr co-doped yttrium-magnesium composite ceramic powder is prepared by ball milling a mixture of yttrium-magnesium composite ceramic, zirconium oxide and zinc oxide. Only the oxide needs to be ball milled, and the process flow is simpler. However, considering the uniformity of material mixing, the particle size of yttrium-magnesium composite ceramic, zirconium oxide and zinc oxide needs to be as small as possible, for example, nano-scale materials. The yttrium-magnesium composite ceramic refers to yttrium-magnesium composite ceramic without Zn-Zr doping. Preferably, the small-particle yttrium-magnesium composite ceramic prepared by the sol-gel method in the first method is selected.

[0040] In an optional embodiment, the sol-gelling comprises: mixing an aqueous solution containing yttrium nitrate, magnesium nitrate, zinc nitrate and zirconium nitrate with citric acid and ethylene glycol, and keeping the mixture at 40-100° C. for 4-36 hours;

[0041] Citric acid as a chelating agent can effectively promote the sol-gel reaction and make the gel self-ignition reaction more complete. However, too much citric acid content will lead to incomplete reaction and more organic matter will remain. When the citric acid content is too little, the complexation effect will be weakened, which will cause uneven distribution of the two phases. Therefore, it is necessary to select a suitable ratio of metal ions and citric acid. Ethylene glycol participates in the reaction as an esterifying agent.

[0042] In an optional embodiment, the molar ratio of magnesium ions to citric acid is 0.5-1;

[0043] In an optional embodiment, the molar ratio of magnesium ions to ethylene glycol is 0.25-0.75;

[0044] In an optional embodiment, the molar ratio of yttrium nitrate to magnesium nitrate in the aqueous solution is 0.5-0.7.

[0045] The concentrations of yttrium nitrate and magnesium nitrate are adjustable and have little effect on the results. The concentration of yttrium nitrate is generally 0.5-1 mol / L, and the concentration of magnesium nitrate is generally 1-2 mol / L.

[0046] ---In an optional embodiment, the combustion step temperature is 100°C-300°C, and the combustion time is 1h-5h; the purpose of combustion is, on the one hand, to remove moisture from the material, and on the other hand, to allow nitrogen to escape in the form of gas, thereby reducing nitrogen residue in the ceramic powder.

[0047] In an optional embodiment, the calcination step temperature is 500° C.-700° C., and the calcination time is 5 h-20 h. After calcination, the calcined product can be crushed and sieved to obtain a Zn-Zr co-doped yttrium magnesium composite ceramic powder with a small particle size.

[0048] In an optional embodiment, the average particle size of the yttrium-magnesium composite ceramic is less than 10 nm;

[0049] In an optional embodiment, the particle size of the zirconium oxide and zinc oxide is less than 40 nm.

[0050] In an optional embodiment, the ball-to-material ratio in the ball milling step is 1:5-9, the diameter of the ball mill is 0.5-3 mm, the ball milling speed is 100-250 rad / min, and the ball milling time is 10-30 h;

[0051] And / or, a dispersant is also added during ball milling, and the mass ratio of the dispersant to the oxide is 1.5-3:1.

[0052] When the Zn-Zr co-doped yttrium-magnesium composite ceramic powder is prepared by ball milling, the particle size of the raw materials and the ball milling conditions need to be limited so that the components can be evenly mixed.

[0053] An embodiment of the present invention further provides a method for preparing a Zn-Zr co-doped yttrium-magnesium composite ceramic, comprising: sintering the Zn-Zr co-doped yttrium-magnesium composite ceramic powder described in the aforementioned embodiment to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic.

[0054] In an optional embodiment, the sintering temperature is 1100° C.-1400° C., and the sintering time is 1.5 h-3 h.

[0055] Generally, when preparing yttrium-magnesium composite ceramics from pure phase yttrium-magnesium composite ceramic powder, the sintering temperature needs to reach 1400°C. The Zn-Zr co-doped yttrium-magnesium composite ceramic powder in the present application can effectively reduce the sintering temperature to 1100°C due to the doping of Zn-Zr.

[0056] The embodiment of the present invention further provides a Zn-Zr co-doped yttrium-magnesium composite ceramic prepared by the method described in the above embodiment, wherein the average grain size of the Zn-Zr co-doped yttrium-magnesium composite ceramic is less than 150nm;

[0057] And / or, the density of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 99.95%;

[0058] And / or, the flexural strength of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 400 MPa;

[0059] And / or, the transmittance of the Zn—Zr co-doped yttrium magnesium composite ceramic to light with a wavelength of 1.5 μm-7 μm is greater than 80%.

[0060] In an embodiment of the present invention, the Zn-Zr co-doped yttrium magnesium composite ceramic prepared from the Zn-Zr co-doped yttrium magnesium composite ceramic powder has higher bending strength and transmittance than the yttrium magnesium composite ceramic not doped with Zn-Zr. The transmittance of the Zn-Zr co-doped yttrium magnesium composite ceramic to light with a wavelength of 1.5 microns can reach 80%.

[0061] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0062] Example 1

[0063] This embodiment provides a method for preparing a Zn-Zr co-doped yttrium-magnesium composite ceramic, comprising the following steps:

[0064] Dissolving, dissolving high-purity (all four oxides are high-purity, with a purity greater than 99.99wt%) yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide in nitric acid to obtain a nitrate solution; wherein; the volume ratio of yttrium oxide to magnesium oxide is 1:1, the mass ratio of zinc oxide to zirconium oxide is 1:2, the total mass of zinc oxide and zirconium oxide in the oxides is 10%, and the concentration of yttrium ions in the nitrate solution is 0.5mol / L;

[0065] Sol gelation, mixing an aqueous solution containing yttrium nitrate, magnesium nitrate, zinc nitrate and zirconium nitrate with citric acid and ethylene glycol, and keeping the mixture at 90°C for 24 hours to obtain a gel, wherein the molar ratio of magnesium ion to citric acid is 0.75, and the molar ratio of magnesium ion to ethylene glycol is 0.5;

[0066] Combustion, combustion temperature is 200℃, combustion time is 3h;

[0067] Calcination, the calcination temperature is 600°C, the calcination time is 8h, and Zn-Zr co-doped yttrium magnesium composite ceramic powder is obtained;

[0068] Ball milling, the ball-to-material ratio of the ball milling is 1:7, the diameter of the ball mill is 1 mm, the ball milling speed is 200 rad / min, the ball milling time is 20 h, and ethanol is added during the ball milling, and the mass ratio of the ethanol to the oxide is 2:1;

[0069] Sintering, the sintering temperature is 1200℃, and the calcination time is 2h to obtain Zn-Zr co-doped yttrium magnesium composite ceramics.

[0070] Embodiment 2-5

[0071] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that the volume ratios of yttrium oxide and magnesium oxide are adjusted to 2:1, 1.5:1, 1:1.5 and 1:2 respectively.

[0072] Embodiment 6-9

[0073] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that in the dissolution step, the mass ratios of zinc oxide to zirconium oxide are 1:1, 1:3, 1:4, and 1:5, respectively.

[0074] Examples 10-12

[0075] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that in the dissolution step, the total mass of zinc oxide and zirconium oxide in the oxide is 1%, 5% and 15% respectively.

[0076] Examples 13-15

[0077] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that in the sol-gel step, the holding temperatures are 40, 70, and 100, respectively.

[0078] Examples 16-17

[0079] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that in the combustion step, the combustion temperatures are 100° C. and 300° C. respectively.

[0080] Examples 18-19

[0081] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that in the sintering step, the sintering temperatures are 1100° C. and 1400° C. respectively.

[0082] Embodiment 20

[0083] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that the mass ratio of zinc oxide to zirconium oxide is 2:1, and the total mass of zinc oxide and zirconium oxide in the oxide is 20%.

[0084] Embodiment 21

[0085] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that the sol-gel temperature is 30° C. and the time is 30 h.

[0086] Embodiment 22

[0087] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that the combustion temperature is 350° C. and the combustion time is 3 h.

[0088] Embodiment 23

[0089] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from the embodiment 1 only in that the calcination temperature is 450° C. and the calcination time is 10 h.

[0090] Embodiment 24

[0091] This embodiment provides a method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, which is different from Embodiment 1 only in that the sintering temperature is 1000° C. and the sintering time is 5 h.

[0092] Embodiment 25

[0093] This embodiment provides a method for preparing a Zn-Zr co-doped yttrium-magnesium composite ceramic, comprising the following steps:

[0094] Ball milling: ball milling a mixture of yttrium-magnesium composite ceramics with an average particle size of 9 nm, zirconium oxide with an average particle size of 40 nm, and zinc oxide with an average particle size of 40 nm to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic powder; wherein the ball-to-material ratio of the ball milling is 1:9, the diameter of the ball mill is 3 mm, the ball milling speed is 150 rad / min, the ball milling time is 15 h, and ethanol is also added during the ball milling, and the mass ratio of the ethanol to the oxide is 1.5:1;

[0095] Sintering, the sintering temperature is 1200℃, and the calcination time is 2h to obtain Zn-Zr co-doped yttrium magnesium composite ceramics.

[0096] Comparative Example 1

[0097] This comparative example provides a method for preparing yttrium-magnesium composite ceramics, which is different from Example 1 only in that zinc oxide is not added in the dissolving step.

[0098] Comparative Example 2

[0099] This comparative example provides a method for preparing yttrium-magnesium composite ceramics, which is different from Example 1 only in that zirconium oxide is not added in the dissolution step.

[0100] Comparative Example 3

[0101] This comparative example provides a method for preparing yttrium-magnesium composite ceramics, which is different from Example 1 only in that zinc oxide and zirconium oxide are not added in the dissolution step.

[0102] The particle size of the Zn-Zr co-doped yttrium-magnesium composite ceramic powder and some properties of the Zn-Zr co-doped yttrium-magnesium composite ceramic prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A Zn-Zr co-doped yttrium-magnesium composite ceramic powder, characterized in that: It comprises yttrium oxide, magnesium oxide, zinc oxide and zirconium oxide, wherein the volume ratio of yttrium oxide to magnesium oxide is 0.9-1.2:1, and the mass ratio of zinc oxide to zirconium oxide is 1:1-5; in the Zn-Zr co-doped yttrium magnesium composite ceramic powder, the total mass fraction of zinc oxide and zirconium oxide is less than 15%.

2. The Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 1, characterized in that: The average particle size of the Zn-Zr co-doped yttrium-magnesium composite ceramic powder is less than 10 nm.

3. A method for preparing the Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 1 or 2, characterized in that: include: The solution including yttrium salt, magnesium salt, zinc salt and zirconium salt is subjected to sol-gelation, combustion and calcination in sequence to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic powder; Alternatively, a mixture of yttrium-magnesium composite ceramics, zirconium oxide and zinc oxide is ball-milled to obtain the Zn—Zr co-doped yttrium-magnesium composite ceramic powder.

4. The method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 3, characterized in that: The sol gelation comprises: mixing an aqueous solution containing yttrium nitrate, magnesium nitrate, zinc nitrate and zirconium nitrate with citric acid and ethylene glycol, and keeping the mixture at 40-100° C. for 4-36 hours; Preferably, the molar ratio of magnesium ion to citric acid is 0.5-1; Preferably, the molar ratio of magnesium ion to ethylene glycol is 0.25-0.75; Preferably, the molar ratio of yttrium nitrate to magnesium nitrate in the aqueous solution is 0.5-0.

7.

5. The method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 3, characterized in that: The combustion step temperature is 100°C-300°C, and the combustion time is 1h-5h; And / or, the calcination step temperature is 500° C.-700° C., and the calcination time is 5 h-20 h.

6. The method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 3, characterized in that: The average particle size of the yttrium-magnesium composite ceramic is less than 10 nm; And / or, the particle size of the zirconium oxide and zinc oxide is less than 40 nm.

7. The method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 3, characterized in that: The ball-to-material ratio of the ball milling step is 1:5-9, the diameter of the ball mill is 0.5-3 mm, the ball milling speed is 100-250 rad / min, and the ball milling time is 10-30 h; And / or, a dispersant is also added during ball milling, and the mass ratio of the dispersant to the powder is 1.5-3:

1.

8. A method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics, characterized in that: include: The Zn-Zr co-doped yttrium-magnesium composite ceramic powder according to claim 1 or 2 is sintered to obtain the Zn-Zr co-doped yttrium-magnesium composite ceramic.

9. The method for preparing Zn-Zr co-doped yttrium-magnesium composite ceramics according to claim 8, characterized in that: The sintering temperature is 1100°C-1400°C, and the sintering time is 1.5h-3h.

10. A Zn-Zr co-doped yttrium-magnesium composite ceramic prepared by the method of claim 8 or 9, characterized in that: The average grain size of the Zn-Zr co-doped yttrium-magnesium composite ceramic is less than 150nm; And / or, the density of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 99.95%; And / or, the flexural strength of the Zn-Zr co-doped yttrium-magnesium composite ceramic is greater than 400 MPa; And / or, the transmittance of the Zn—Zr co-doped yttrium magnesium composite ceramic to light with a wavelength of 1.5 μm-7 μm is greater than 80%.

Citation Information

Patent Citations

  • Infrared transparent ceramic material and preparation method thereof

    CN109369183A

  • Yttrium oxide-magnesium oxide infrared multiphase ceramic and preparation method thereof

    CN113716963A

  • Nano multiphase infrared transparent ceramic material and preparation method thereof

    CN113956041A

  • Preparation method for fluorescent ceramic and fluorescent ceramic

    WO2021135883A1

Cited By

  • Low-scattering-loss high-transmission composite ceramic and preparation method thereof

    CN122878138A